WATER BUDGET CALCULATION BY SPATIAL MODELING DATA: study applied to basin of Buena Vista river, Ecuador - Cecilia Coral, Ana [UNESP]; Garcia Tommaselli, Jose Tadeu [UNESP]; Leal, Antonio Cezar [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2015)
In this paper discussed the methodological process to calculate the monthly average water balance of a watershed located in the coastal region of Ecuador, in order to show the roll of the vegetation on the water dynamics. The method uses GIS tools to estimate the soil water balance based on the classic methodology of Thornthwaite and Mather, which allows calculating the water regime from the definition of the maximum available water capacity in the soil, the measurement (average or total) of precipitation and potential evapotranspiration estimated by Thornthwaite. GIS environment allowed water balance estimation through map algebra applied to continuous surfaces. The intermediate and final products of this simulation exercise (i.e. models) are raster layers or space-temporal matrices representing average water condition in scales of time (monthly) and space (pixel) in the study watershed. Sampling of partial and final results was performed to verify the accuracy of the proposed methodology. Based on the results of this comparison was assessed that the proposed methodology presents satisfactory results and can be applied to larger units of analysis.
Keywords: Watershed; water balance; GIS; spatial modeling